BEYOND NUMBERS: UNRAVELING THE IMPACT OF HUMAN CAPITAL, BUSINESS SIZE, AND IT ON DATA ACCURACY - Riyanto, Naomi Fani; Rapina; Martusa, Riki; Meythi; Gunawan, Johanes Felix (LEMBAGA PENERBIT FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS TRISAKTI, 2025)
This study aims to analyze the influence of human resource competence, firm size, and the utilization of information technology on the quality of financial reporting. Financial reports serve as a crucial tool for conveying information about a company's business activities to the public. Micro, Small, and Medium Enterprises (MSMEs), which operate independently, contribute significantly to Indonesia's economy, particularly in absorbing a large portion of the workforce. Proper financial reporting is essential for MSMEs to monitor operational costs, understand financial conditions such as profit and loss, manage debts, and fulfill tax obligations accurately. This study employs a quantitative method with a survey approach. Data were collected through questionnaires distributed to MSMEs in Bandung City. The sample consists of 82 randomly selected respondents. The collected data were analyzed using SEM-PLS. The results indicate that human resource competence and the utilization of information technology have a positive and significant impact on the quality of financial reporting. However, firm size does not influence the quality of financial reporting. MSMEs with adequate human resource competence tend to have high-quality financial reporting. MSMEs that utilize information technology also tend to have a better financial reporting system.